Pedagogia da diversidade: a contribui????o do N??cleo de Estudos Afro-Brasileiros (NEAB) da Universidade Federal do ABC (UFABC) para a forma????o continuada dos (as) professores (as) no contexto de uma educa????o antirracista - Oliveira, Daniela Pinheiro de (2020)
The present study, entitled Pedagogy of diversity: the contribution of the Nucleus of Afro-Brazilian Studies (NEAB) of the Federal University of the ABC (UFABC) to the continuing education of teachers in the context of an antiracist education, aims to investigate and analyze the continuing education offered by the Nucleus of Afro-Brazilian Studies of the Federal University of the ABC and its repercussions on the teaching practice of its students, in the confluence of awareness for an antiracist education. The problem that stimulated this research was the concern due to the disarticulation between knowledge, practices and speeches in the classroom, since many teachers did not have, in their initial formation, subjects that approached in an integral way the Afro-Brazilian history and culture. To become aware of the research problem, let us start from the question that has been formulated: having as a universe of research the Nucleus of Afro-Brazilian Studies (NEAB), of the Federal University of the ABC, how does the formation of the teacher with a view to the implementation of the studies of African and Afro-Brazilian history and culture - as provided in Federal Law No. 10.639/2003 - contribute to his teaching practice, at the confluence of awareness for an antiracist education? This work started from the hypothesis that the continuous formation, carried out in the referred NEAB, contributes to increase the awareness of the students, so that they opt for a pedagogical practice based on strategies to combat ethnic-racial inequalities, situations of racism and prejudice, in educational spaces. From the methodological point of view, a qualitative approach was used, with resources and analysis of institutional documents and the analysis of interviews with teachers. The analysis was carried out by means of the following categories: continuous teacher training for diversity pedagogy and awareness and antiracist education, with reference to the works of educators Paulo Freire, Nilma Lino Gomes and Kabengele Munanga. The set of data analyzed made it possible to identify the commitment of NEAB UFABC in the formative dimension, the organization of support contents and the great support of the teachers to concretize the formations. The analysis of the interviews pointed out the commitment of the course participants to the current historical-social context, in dealing with the reproduction of the Eurocentric mechanisms that control the history of erasure that divides the world and reaffirms the hegemonic discourse, as well as the awareness of the need for continuous training in studies that encompass African and Afro-Brazilian history and culture, in order to contribute to pedagogical strategies in the classroom that aim to combat ethnic-racial inequalities, situations of racism and prejudice in educational spaces. The results allow us to conclude that NEAB UFABC was inaugurated in 2017, well after the enactment of law 10.639/03, presents in its purposes regarding the continued training of teachers and its results, the dissemination for education of ethnic-racial relations, in line with the legal bases.